Quercetin: the bioactive compound from Allium cepa L. as anti-inflammation based on in silico screening - Mohamad Amin; Kurniawan Setia Putra; Ihya Fakhrurizal Amin; Nanda Earlia; Dina Maulina; Betty Lukiati; Umie Lestari (Biology, Medicine, & Natural Product Chemistry, 2018)
Inflammation is a tissue injury that occurs due to physical trauma or microbiological substances that involve the activities of many cell types. Inflammation can be prevented using the natural medicines from Allium cepa L. Quercetin is one of the bioactive compounds found in Allium cepa L and has been reported to have anti-inflammatory activity. The natural medicines have been used to minimize non-steroidal anti-inflammatory drugs. This study aims to investigated the modeling structures and the protein receptor from quecertin in inflammation mechanism and their optimization of the effectiveness in the human body. The bioinformatics tools used in this study are the database of quercetin compounds, Pubchem and Swis Target Prediction protein prediction databases, PyRx 0.8 molecular docking software, ligand docking, and binding site analysis with PyMOL and LigPlus software. The results from in silico show that quercetin compounds can interact with Muscleblind-like protein 1 target protein with a Binding Affinity minus value which is not much different from the dexamethasone compound. Dexamethason is a standart because it is a corticosteroid drug that can be used as an anti-inflammatory to reduce inflammation, allergic reactions, arthritis and other inflammatory diseases.